Pengenalan Teknologi pada Anak dan Manajemen Usaha pada Orang Tua untuk Mampu Membentuk Karakter Anak sambil Bekerja - L. Jatmiko Jati; Rini Anggriani; Helna Wardhana; Rizka Darmayanti; Zulfiana; Kartika Lestari (Jurnal Ilmiah Pengabdian dan Inovasi, 2022)
After the research team made observations in Pegondang Hamlet, the research team found that several parents deliberately gave smartphones to their children who were even toddlers with minimal supervision and some had businesses that had to be taken care of. Therefore, the research team felt the need to educate the relationship between technology and children and how to manage business for parents who sell while taking care of children. The method chosen by the research team in carrying out this Community Service activity is PAR (Participatory Action Research). Community Service Activities with the theme of Free Children's Seminar with Prizes are able to change parents' views regarding the use of smartphones and the introduction of technology in children. This service activity is also able to provide solutions for parents who are busy in business to remain able to carry out their role in raising children well through business management.